TWEAK/Fn14 Activation Participates in Ro52-Mediated Photosensitization in Cutaneous Lupus Erythematosus - Liu, Yale; Xu, Meifeng; Min, Xiaoyun; Wu, Kunyi; Zhang, Ting; Li, Ke; Xiao, Shengxiang; Xia, Yumin (Frontiers in Immunology, 2017)
Tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) binds to its sole receptor of fibroblast growth factor-inducible 14 (Fn14), participating in various inflammatory responses. Recently, TWEAK/Fn14 activation was found prominent in the lesions of cutaneous lupus erythematosus (CLE). This study was designed to further reveal the potential role of this pathway in Ro52-mediated photosensitization. TWEAK, Fn14, and Ro52 were determined in the skin lesions of patients with CLE. Murine keratinocytes received ultraviolet B (UVB) irradiation or plus TWEAK stimulation, and underwent detection for Ro52 and proinflammatory cytokines. The chemotaxis of J774.2 macrophages was evaluated on TWEAK stimulation of cocultured keratinocytes. We found that TWEAK, Fn14, and downstream cytokines were highly expressed in CLE lesions that overexpressed Ro52. Moreover, TWEAK enhanced the UVB-induced Ro52 upregulation in murine keratinocytes. Meanwhile, TWEAK stimulation of keratinocytes favored the migration of macrophages through promoting the production of chemokine C-C motif ligands 17 and 22. Furthermore, Fn14 siRNA transfection or nuclear factor-kappa B (NF-κB) inhibitor abrogated the TWEAK enhancement of Ro52 expression in keratinocytes. Similarly, TNF receptor associated factor 2 (TRAF2) siRNA reduced the protein level of Ro52 in these cells upon TWEAK stimulation. Interestingly, UVB irradiation increased the expression of TNF receptor type 1 (TNFR1) but not affecting TNFR2 expression in keratinocytes. In conclusion, the TWEAK/Fn14 signaling participates in Ro52-mediated photosensitization and involves the activation of NF-κB pathway as well as the function of the TRAF2/TNFR partners.